2022
DOI: 10.21037/atm-22-4337
|View full text |Cite
|
Sign up to set email alerts
|

The recycling of AMPA receptors/GABAa receptors is related to neuronal excitation/inhibition imbalance and may be regulated by KIF5A

Abstract: Background: Excitation/inhibition imbalance (E/I imbalance), which involves an increase of alphaamino-3-hydroxy-5-methyl-4-isoxazole (AMPA) receptors (AMPARs) and decrease of gamma-aminobutyric acid type A (GABA) type A receptors (GABAaRs) on the neuron surface, has been documented in the pathogenesis of seizures. Notably, it has been established that both the glutamate receptor subunit 2 (GluR2) of AMPARs and beta 2/3 subunits of GABAaRs (Gabrb2+3) participate in the recycling mechanism mediated by the kinesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The primary neuron culture was carried out according to the method of Li et al 27 When the neurons had been cultured for 7 days, the neurons were identified and exposed to the drugs. The neurons in different wells were randomly grouped.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary neuron culture was carried out according to the method of Li et al 27 When the neurons had been cultured for 7 days, the neurons were identified and exposed to the drugs. The neurons in different wells were randomly grouped.…”
Section: Methodsmentioning
confidence: 99%
“…We used Digidata 1550B patch‐clamp amplifier to obtain electrophysiology of neurons. The neuronal action potentials were performed according to the method of Li et al 27 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GABAaRs are first assembled in the endoplasmic reticulum and then undergo palmitoylation once transported to the Golgi body, which enhances the hydrophobicity of proteins and promotes the translocation of receptors through the Golgi apparatus to the plasma membrane and synapses [ 51 ]. Previous reports have shown that the number and location of GABAaRs on the cell membrane keep changing [ 51 ] and can be dynamically regulated through neuronal excitability processes, including movement [ 52 ], internalization [ 35 ], and recycling [ 53 , 54 ] of the receptors. These processes are also referred to as GABAaR dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Excitation/inhibition imbalance underlies numerous pathological conditions ( 5 , 9 ). Given our previous findings that inhibiting the excitability of PVN neurons can alleviate visceral pain ( 5 ), we hypothesized that GABAergic neurons—the primary inhibitory neurons—are involved in regulating visceral pain.…”
Section: Introductionmentioning
confidence: 99%